Ultrasound Therapeutics - A Review - Zhang, Xiao-ying; Zhang, Pei-ying (Current Medical Imaging, 2017)
Ultrasound is a form of mechanical waves that can traverse non-invasively through the human body up to some extent. Because of this non-invasive ability to penetrate through tissues and reflect back, ultrasound has found many applications in medicine for imaging inner organs to understand pathology and help diagnosing disease and also for therapeutic applications such as low back pain treatment, as ultrasound waves transmit energy and can generate local heat production in a focused area. In this article, we have reviewed the current state of knowledge on the therapeutic applications of ultrasound in the injuries of cartilage, knee joint, fresh bone fractures, and also cancers. While low intensity ultrasound has been found to act as an anabolic stimulator for cartilage regeneration, high intensity focused ultrasound has applications in precise tissue ablation of different types of tumors. Further, role of ultrasound in micro bubble mediated ultrasound therapy has been discussed for the efficient delivery of intravascularly administered drugs or genes to targeted tissues during cancer.
Keywords: Cancer